THE RACIAL AND ETHNIC EVOLUTION OF THE IRANIAN PLATEAU - Mason Baronian (Frontline Social Sciences and History Journal, 2024)
The Iranian Plateau, a region of significant historical and cultural importance, has been a crossroads for various civilizations and ethnic groups over millennia. This study explores the racial and ethnic evolution of the Iranian Plateau, examining the complex interplay of migration, conquest, and cultural exchange that has shaped the demographic landscape of this area. By analyzing archaeological evidence, historical texts, and genetic studies, the research traces the origins and movements of early inhabitants, including Aryan, Elamite, Median, and Persian groups, and highlights the influence of external cultures such as the Greeks, Arabs, Turks, and Mongols. The study also investigates the social and cultural integration processes that led to the formation of a unique Iranian identity, reflecting a blend of diverse ethnic and racial elements. This work aims to provide a comprehensive understanding of how historical events and interactions have contributed to the rich mosaic of ethnicities and cultures that define the Iranian Plateau today.